Antioxidant Capacity and Profiles of Phenolic Acids in Various Genotypes of Purple Wheat - Shamanin, Vladimir P.; Tekin-Cakmak, Zeynep H.; Gordeeva, Elena I.; Karasu, Salih; Pototskaya, Inna; Chursin, Alexandr S.; Pozherukova, Violetta E.; Ozulku, Gorkem; Morgounov, Alexey I.; Sagdic, Osman; Koksel, Hamit (MDPI, 2022)
The total phenolic content, phenolic compositions, and antioxidant capacity in the grain of 40 purple wheat genotypes were studied. In this study, purple wheats were investigated in terms of their composition of free and bound phenolic acids and 2,2-diphenyl-1-picrylhydrazyl radical scavenging capacity. The free phenolic content ranged from 164.25 to 271.05 mg GAE/100 g DW and the bound phenolic content was between 182.89-565.62 mg GAE/100 g wheat. The total phenolic content of purple wheat samples ranged from 352.65 to 771.83 mg GAE/100 g wheat. Gallic acid, protocatechuic acid, catechin, 4-hydroxybenzoic acid, syringic acid, ellagic acid, m-coumaric acid, o-coumaric acid, chrysin, caffeic acid, p-coumaric acid, ferulic acid, quercetin, kaempferol, rutin, sinapic acid, and chlorogenic acid were detected by HPLC system. Gallic acid, benzoic acid derivatives, and dominant phenolics, which are frequently found in cereals, were also dominant in purple wheat samples and were found in free fractions. The antioxidant capacity was assessed using the DPPH method. The antioxidant capacity (AA%) in the free phenolic extracts of the purple wheats was between 39.7% and 59.5%, and the AA% values of bound phenolic extract of the purple wheat varied between 42.6% and 62.7%. This study suggested that purple wheat samples have high phenolic compound content as antioxidant potential and therefore consumption of purple wheat-containing food products may provide health benefits.
Keywords: free phenolic; bound phenolic; purple wheat; gallic acid; TRITICUM-AESTIVUM; GRAIN WHEAT; IDENTIFICATION; FRACTIONS; TURGIDUM; COLOR; BREAD; Food Science & Technology